The nurse's performance in the nutritional care of the obese child (Research, Society and Development, 2020)
It is a bibliographic study carried out between April and May 2017 to October 2019, in scientific articles and revised books referring to nursing consultation. The study aims to identify how the nurse can act in the infant nutrition of the obese child with a view to preventing aggravating situations in the health of the obese child, establishing with the family or responsible the benefits for a complete growth and development. The selected studies show that with the nursing consultation bringing information about weight and other anthropometric indices, it brings to the family, mother / caregiver the importance of assistance during feeding, thus creating a bond of trust and respect between the nurse and the responsable. Due to the growth of childhood obesity, it is necessary to rethink certain parameters and seek to stimulate society so that the next generation will have a little more quality of life.